Joint Hybrid and Passive Beamforming for Millimeter Wave Symbiotic Radio Systems - Yang, Gang; Wei, Tao; Liang, Ying-Chang (IEEE wireless communications letters, 2021)
Symbiotic radio (SR), which enables a backscatter device (BD) to transmit information to a primary receiver (PR) by modulating primary signals, has emerged as an energy-, spectrum-, and cost-efficient communication technology for Internet-of-Things. This letter studies a millimeter wave (mmWave) SR system in which a primary transmitter (PT) sends information to a PR via mmWave communication. We maximize the achievable rate of the backscatter link subject to the rate constraint of the direct link, by jointly optimizing the PT's hybrid beamforming (HBF) and the BD's passive beamforming (PBF). An iterative algorithm based on alternating optimization is proposed to solve the formulated non-convex problem. Numerical results show that the optimal joint-beamforming design enhances the backscatter-link rate significantly compared to the benchmark with only HBF.